Antioxidant defense system responses, lysosomal membrane stability and DNA damage in earthworms (Eisenia fetida) exposed to perfluorooctanoic acid: an integrated biomarker approach to evaluating toxicity. Issue 43 (3rd August 2021) - Wang, Zhifeng; Li, Chaona; Shao, Yuanyuan; Xue, Weina; Wang, Ning; Xu, Xiaoming; Zhang, Zhibin
Abstract : The integrated biomarker response (IBR) index was calculated to evaluate the integrated toxicological effects of PFOA on earthworm Eisenia fetida . Abstract : Perfluorooctanoic acid (PFOA) is one of the most representative perfluoroalkyl substances and has garnered intense human and ecological health concerns due to its ubiquity in the environment, bio-accumulative nature and potential toxicological effects. In this study, an artificial soil containing PFOA was used to evaluate the biological toxicity of PFOA to earthworms Eisenia fetida . Six kinds of oxidative stress biomarkers, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST), reduced glutathione (GSH) and lipid peroxidation (LPO), as well as lysosomal membrane stability (LMS) and DNA damage in earthworms were detected after exposure to 0, 10, 20, 40, 80 and 120 mg kg −1 PFOA in the soil for 3, 7, 14, 28, and 42 days. The results of multi-biomarker responses indicated that PFOA can induce various adverse effects on earthworms, including growth inhibition, oxidative stress and genotoxicity, resulting in lipid membrane peroxidation, decreased lysosomal membrane stability and DNA damage. LPO, LMS and DNA damage all presented dose- and time-dependent relationships. An integrated biomarker response (IBR) index was applied to summarize the multi-biomarker responses to star plots, and the IBR value was calculated as the area of the plots to indicate the integrated stress of PFOA on earthworms. The IBR index showed that the integrated stress induced by PFOA increased markedly throughout the exposure period, exhibiting a concentration-related and exposure time-related effect. The graphical changing trend of the IBR star plots, along with the multi-biomarker responses, suggested that the biomarkers of the antioxidant defense system in earthworms are sufficiently sensitive for short-term PFOA biomonitoring programs, while the bioindicators that indicate actual damage in organisms are more suitable to be employed in long-term monitoring programs for the risk assessment of PFOA. This is the first study evaluating the biological toxicity of PFOA by using an integrated biomarker approach. Our results showed that PFOA can potentially damage soil ecosystems, which provides valuable information for chemical risk assessment of PFOA in the soil environment and early warning bioindicators of soils contaminated by PFOA.